Environment (India, 2023)
To help students in acquiring the essentials of the topic 'environment$1 (Bduring preparation for Civil Services Examination, Shankar IAS Academy has brought the book, 'environment$1 (B. This book follows the paper pattern and syllabus given by Union Public Service Commission which conducts these examinations. The language of the book is simple and the content is engaging which ensures students face no trouble during studying. Plus the distinctive designing makes it easy to navigate and read. This bestseller book has sold over 30, 000 copies and is widely read by students. A team of highly experienced writers from Shankar IAS Academy have written this book and hence it is accurate and reliable. The updated syllabus of UPSC focuses a lot on environment.s
English
Keywords: Civil service examinations; Biodiversity; Biology; Climate change; Environment